The Influence of Service Quality and Communication Moderated by Patient Trust on Patient Satisfaction - R. P. Hutadjulu, Rebecca; Budidharmanto, Lexi Pranata; Padmalia, Metta (Journal Research of Social Science, Economics, and Management, 2026)
The growth of the healthcare industry in North Sulawesi has driven existing hospitals to continuously enhance the quality of their services. RSUP Prof. Dr. R. D. Kandou Manado, operating since 1995, now faces increasing competition from newly established hospitals and must therefore innovate its patient care services. This research intends to examine the influence of service quality and communication quality on patient satisfaction, with patient trust as the moderating variable. The study was conducted using a quantitative approach, employing Structural Equation Modeling (SEM) with a multivariate statistical analysis method through Smart-Partial Least Square (Smart-PLS). The survey was carried out in the North Sulawesi region by distributing questionnaires via social media from May 2024 to April 2025. The findings indicate that service quality, when moderated by patient trust, significantly affects patient satisfaction, whereas communication quality moderated by patient trust does not show a significant effect on patient satisfaction. This study confirms that service quality significantly enhances patient satisfaction when moderated by patient trust. In contrast, communication quality, even when moderated by trust, does not significantly impact satisfaction. These findings highlight the central role of trust in amplifying the effect of service quality, offering practical guidance for hospitals to focus on service excellence and trust-building as key drivers of patient satisfaction.